RANCANG BANGUN SISTEM PENGEREMAN REM TROMOL PADA SEPEDA LISTRIK BERBASIS ARDUINO UNO R3 - Slamet Riyadi,; Leo Anggar Prasetyo,; Novita Wulandari, (Journal of Innovation Research and Knowledge, 2025)
Braking failure due to overheating is more common in electric bicycles used for long distance travel or in hilly areas. This study prompted manufacturers to develop more effective cooling systems for brakes. (Study from the European Transport Safety Council (ETSC)), the objectives of this research are as follows: To find out how to make a drum brake braking system on an electric bicycle using Arduiono Uno R3 as a teaching tool to understand the function and workings of the system, To detect braking temperature and provide a warning system. This research is generally research that aims to develop a media. The appropriate research method for this research is the Research and Development Method or also known as Research and Development (R&D)". Based on the test results, it shows that in the process of three tests with a distance of 1 km, speed of 11 km/hour, 13 km/hour, 15 km/hour and the same load, namely 80 kg. The braking temperature is still safe with a maximum temperature of 26°C. The buzzer and LED lights do not turn on, because the temperature limit is 40°C on the Arduino Uno R3 Braking temperature using the Arduino Uno R3 based electric bicycle drum brake works optimally according to a predetermined program and is safe to use. Designing the drum brake braking system on an Arduino Uno R3 based electric bicycle involves several important stages to ensure the system can function properly. Planning and concept design, namely identifying needs, determining the functions and components needed such as temperature sensors, LCD screens, LED lights, resistors, buzzers, temperature modules, batteries, jumper cables, breadboard and Arduino Uno R3 as the brain of the microcontroller system. Coding and testing is coding the Arduino program to detect temperature, receive input from sensors, and set temperature limits. Tests carry out comprehensive system testing, including LCD screen tests, LED tests, buzzer tests and sensor tests to detect heat temperatures